GLOBAL BRAND – LOCAL CHOICE: PENGARUH BRAND IMAGE DAN COUNTRY OF ORIGIN TERHADAP CONSUMPTION MELALUI PURCHASE INTENTION - Oliandes Sondakh; Felicia Nadya Isabel; Renna Madgalena (Faculty of Economics and Business Universitas Pelita Harapan, 2025)
The Food and Beverages (F&B) industry is one of the important sectors in Indonesia. Chairman of the Indonesian Franchise Association at the 22nd International Franchise, License, and Business Concept Expo and Conference 2024, said that the franchise business in Indonesia is dominated by foreign brands. The large potential of the Indonesian market for the F&B industry is what then causes the emergence of tight competition between foreign brands and local brands, so that in the end many are unable to compete. However, there is one brand of ice cream and tea drinks from China, Mixue Ice Cream & Tea, which has started expanding its business overseas since 2018 and is still surviving in the international market. The very fast development of business in just three years (2018 – 2021), makes it interesting to conduct research on the factors that influence consumers to purchase F&B products. This research uses a quantitative approach with a causal research type with a cross-sectional method. This research uses multivariate analysis Partial Least Square-Structural Equation Modeling (PLS-SEM), which focuses on variance to handle the complexity of research models involving several latent variables. The research results show that Brand Image and Country of Origin have a positive and significant effect on Consumption through the mediation of Purchase Intention. These findings imply that marketing strategies should prioritize building a strong and trustworthy brand and effectively communicating the product's country of origin to strengthen consumers' purchase intentions, which in turn increases the likelihood of consumption.